Factors Indicating Well-Being of Employees in Firework Industries - Dr.KM Ashifa (Drugs and Cell Therapies in Hematology, 2021)
Present investigation trying to analyze factors indicating the well- being issued for the employees in firework industries. Fireworks industry is a very flourishing industries in Tamil Nadu, India especially in Sivakasi district. In fireworks the employees have lot of risk on their safety and well being. There has been lot of health afflictions due to air quality. The firework industry required to implement more safety measure as compared to others due to high-risk nature of the work with fireworks. But unfortunately, it is hardly find proper safety and welfare measures undertaken by the administration for the welfare of workers. Officials of the state and central government organisation should help in implementation of safety system in fireworks units in Sivakasi to ensure misfortune free fireworks industry. So the study is referring to the main intention of to discover the safety measures in the fireworks industry. According to the factories act the safety instrument should be very important because the safety of the employees is very essential. In fireworks industry lot of fire disaster is happening this is a time to identify the safety materials and well-being of the employees.